Handmade Patient-Specific Bolus Combined With Photon Radiation Therapy for Skin Cancer - Mostafa Robatjazi; Sajedeh Sadat Jamalabadi; Sajjad Beynabaji; Hamid Reza Baghani; Seyed Alireza Javadinia (Case Reports in Oncological Medicine)
Conclusion: This case report supports the effectiveness of handmade boluses in combination with 6 MV photons for skin cancer RT, particularly in resource-constrained settings where advanced treatment modalities may not be readily available. The handmade bolus approach provides an accessible solution to enhance the precision of skin cancer RT.